2008
DOI: 10.1590/s0102-71822008000100008
|View full text |Cite
|
Sign up to set email alerts
|

Transexualidade: corpo, subjetividade e saúde coletiva

Abstract: RESUMO: O artigo discute o atendimento a pacientes transexuais na rede pública de saúde, a partir de uma pesquisa exploratória realizada no Hospital Universitário Clementino Fraga Filho, da Universidade Federal do Rio de Janeiro (HUCFF/UFRJ), com transexuais que procuraram atendimento com o objetivo de realização de cirurgia de transgenitalização. Observa-se que a transexualidade se caracteriza por uma condição de intenso sofrimento. Esta experiência se dá não apenas por uma percepção de não pertencimento ao s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 3 publications
0
2
0
12
Order By: Relevance
“…It is unacceptable that the transsexual is bound to live in a body that does not represent him and which does not translate his soul. In reality, this condition, if not addressed and worked on, can cause a human being to destroy himself gradually, making his life unfeasible and "unlivable 21 . A study of transsexuals reported intense psychic suffering, which was translated into depression, suicide attempts, distress, eating disorders, not only by biological conflict, but also by social consequences of this condition 21 .…”
Section: Has Determined? "Transsexuality Is a Matter Of Identity It mentioning
confidence: 99%
See 1 more Smart Citation
“…It is unacceptable that the transsexual is bound to live in a body that does not represent him and which does not translate his soul. In reality, this condition, if not addressed and worked on, can cause a human being to destroy himself gradually, making his life unfeasible and "unlivable 21 . A study of transsexuals reported intense psychic suffering, which was translated into depression, suicide attempts, distress, eating disorders, not only by biological conflict, but also by social consequences of this condition 21 .…”
Section: Has Determined? "Transsexuality Is a Matter Of Identity It mentioning
confidence: 99%
“…In reality, this condition, if not addressed and worked on, can cause a human being to destroy himself gradually, making his life unfeasible and "unlivable 21 . A study of transsexuals reported intense psychic suffering, which was translated into depression, suicide attempts, distress, eating disorders, not only by biological conflict, but also by social consequences of this condition 21 . There are innumerous barriers to accepting one's body, including some that are maintained and underpinned by the very insecurity and psychological vulnerability of the affected person.…”
Section: Has Determined? "Transsexuality Is a Matter Of Identity It mentioning
confidence: 99%
“…O corpo é objeto de estudo de Patricia Porchat que, em seu artigo (2014) Também foram identificados trabalhos que objetivam identificar ou narrar os processos de transição das pessoas transexuais, tendo suas decisões de modificações corporais e produções de corporalidades como elementos de partida, sinalizam sobre a importância de não uniformizar as experiências das pessoas transexuais, considerando que estas comportam "várias formas singulares de subjetivação", não cabendo assim em traduções apressadas de estruturas de personalidade ou modos de funcionamento característicos, refletindo também sobre a diversidade do desejo e os riscos de se tentar encaixar a transexualidade numa matriz heteronormativa (Arán, Zaidhaft, & Murta, 2008;Arán, Murta, & Lionço, 2009;Lionço, 2009;Monteiro & Nardi, 2009;Garcia, 2012;Silva & Oliveira, 2013;Canella Filho, 2013;Freitas, 2014;Dias, 2015, Vasconcelos, 2015.…”
Section: Conhecimento Fundacional E Consciênciaunclassified
“…Os estudos que criticam as normas do processo transexualizador como condição de acesso aos cuidados em saúde seriam os primeiros identificados, na pesquisa, a relacionar saúde como direito humano e princípio doutrinário do SUS (Arán, Zaidhaft, & Murta, 2008;Arán, Murta, & Lionço, 2009;Lionço, 2006Lionço, , 2009Amaral, 2007;Amaral, 2011;Mack, 2015).…”
Section: Estigma Discriminação E Barreiras Para O Cuidadounclassified
See 1 more Smart Citation